Financial, Economic, and Stakeholder Analysis of Milk Processing Plant in Ethiopia - Maydanik, Inna (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Milk is one of the main sources of income for many pastoralists around the world. The Somali Region in Ethiopia is famous for its high density of livestock, implying that is has a significant potential for milk production. The perishable nature of the milk and the absence of the milk processing facilities are two of the main factors that reduce this region’s ability to utilise the opportunity of milk production, which imposes significant economic losses on the community as a whole. This study assesses the financial and economic feasibility of the milk processing plant in Ethiopia region, Jijiga city, and analyses alternatives for the implementation of the milk processing plant using the integrated method of investment appraisal. Distributive analysis is also used to estimate the allocation of benefits to the government of Ethiopia, the pastoralists and traders supplying milk to the plant, the labour that is employed by the facility, the Jijiga city community and lastly the private entrepreneur. Sensitivity analysis is used to assess potential risk factors facing the facility. The results of the analysis showed that the financial net present value of the project is positively promising that the benefits would be greater than its costs. The implementation of such an intervention significantly increases the annual income of the pastoralists and decreases the risks of investment for the private sector. It also will increase the demand for the pasteurization of milk and decrease the amount of raw milk available for the locals which is extremely dubious in that area. The economic analysis reveals that the economic net present value is also positive and not only reduces the risk for the private entrepreneur and stakeholders but will be also benefit the economy of Ethiopia. The project is proposed with the motive to develop and promote the Ethiopian agricultural business by leading it to a market oriented level. An improvement in the lifestyle of the locals is expected to follow, as a result of the creation of more job opportunities, improvement of nutrition, and the development of the dairy system of that region. Several stakeholders such as the suppliers of the milk, milk traders, the private entrepreneur, employees, the community, and the government will benefit from the implementation of the project. Keywords: Investment Appraisal, financial analysis, economic analysis, stakeholder analysis, milk processing plant, camel’s milk, cow’s milk, dairy, Ethiopia

ÖZ : Dünya çapinda, geçimini hayvancılıkla sağlayanların temel gelir kaynaklarından biri süttür. Etiyopya’nın Somali bölgesi besi hayvancılığın çok yaygın olmasından dolayı kayda değer süt üretme potansiyeline sahiptir. Fakat, sütün çabuk bozulan yapısı ve sütü işleme olanaklarının yokluğu nedeniyle sektörde tam verimlilik sağlanamamakta ve bu gerçek ciddi ekonomik kayıplara yol açmaktadır. Bu çalışma Etiyopya’nın Jijiga şehrindeki bir süt işleme tesisinin finansal ve ekonomik fizibilitesini değerlendirmektedir. Süt işleme tesisini hayata geçirmenin yatırım projeleri değerlendirme yöntemleriyle analizi yapılmıştır. Bu bağlamda, sözkonusu projenin net gelirinin Etiyopya hükümeti, geçimini hayvancılıkla sağlayanlar, sütü tesise taşıyan tüccarlar, tesiste çalışan işçiler, Jijiga halkı ve özel girişimci arasında nasıl paylaşıldığı hesaplanmıştır. Son olarak, projenin karşı karşıya olduğu potansiyel risk faktörleri duyarlılık analizi kullanılarak hesaplanmıştır. Anahtar Kelimeler: Yatırım Değerlendirmesi, Finansal Analiz, Ekonomik Analiz, Paydaş Analizi, Süt İşleme Tesisi, Deve Sütü, İnek Sütü, Sütçülük, Etiyopya.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2016. Supervisor: Prof. Dr. Hatice Jenkins.
Keywords: Banking and Finance; Dairy plants - Milk trade - Ethiopia; Investment Appraisal; financial analysis; economic analysis; stakeholder analysis; milk processing plant; camel’s milk; cow’s milk; dairy; Ethiopia